Could elective cesarean sections influence the birth weight of full-term infants? - Murta, Eddie Fernando Candido; Freire, Guilherme Carvalho; Fabri, Daniel Capucci; Fabri, Renato Humberto (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: There are no studies on birth weights among full-term infants born by means of elective cesarean section. We aimed to study this in private and public hospitals. DESIGN AND SETTING: Retrospective study at Universidade Federal do Triângulo Mineiro, Uberaba, Brazil. METHODS: Data were collected from the municipal medical birth register of Uberaba from January to December 2000. The data obtained (maternal age, type of delivery, number of prenatal care visits and birth weight, from full-term pregnancy) from the university hospital (UH), which is a tertiary hos- pital that only attends patients within the National Health System (SUS), were compared with data from four private hospitals (PHs) that attend health insurance plans and private patients. Student’s t test, x2 test and multiple logistic regression were used for statistical analysis, with the significance level set at p < 0.05. RESULTS: In the PHs, 1,100 out of 1,354 births (81.2%) were by cesarean section and in the UH, 373 out of 1,332 (28%). Birth weight increased significantly in association with increasing num- bers of prenatal care visits, except for cesarean section cases in PHs. Birth weights among vagi- nal delivery cases in PHs were greater than in the UH (p < 0.05), but this was not observed among cesarean section cases. Multiple logistic regression showed that there was greater risk of low birth weight in PHs (odds ratio: 2.33; 95% confidence interval: 1.19 to 4.55). CONCLUSION: Elective cesarean section per- formed in PHs may be associated with low birth weight among full-term infants.